English teaching in the elementary school: Some critical issues - Clavijo, Amparo (Colombian Applied Linguistics Journal, 2016)
Although for the last 10 years Colombia has proposed a National Plan for Bilingualism in different stages, the education of young children in Colombian public and private schools in relation to English language learning evidences some critical issues regarding the preparation of future teachers, the professional development of in-service teachers, and the national standards for foreign language teaching.